Longitudinal Prediction of Mid‐Adolescent Psychosocial Outcomes From Early Adolescent Family Help Seeking and Family Support. (17th February 2014) - Heerde, Jessica A.; Toumbourou, John W.; Hemphill, Sheryl A.; Olsson, Craig A.
<x xml:space="preserve">Abstract</x> This study examined whether family help seeking and family support represented the same or distinct constructs and prospective associations between emergent constructs and psychosocial outcomes. Data were from 1, 713 school‐based adolescents participating in a randomized controlled trial, in Victoria, Australia. Family help seeking emerged as a single factor, distinct from family support, and was prospectively associated with improved psychosocial outcomes. Father closeness predicted lower depressive symptoms. Family help seeking predicted higher help seeking for peers. Interactions between family help seeking and family support on psychosocial outcomes were not apparent. Findings highlight the importance of examining family help seeking and family support separately in future studies of adolescents' help‐seeking behavior.